Peran Faktor Internal Dan Faktor Eksternal Pada Keberlangsungan Start-Up Bisnis Kota Surabaya - Fransisca Desiana Pranata Sari; Sri Nathasya Br Sitepu (Universitas Airlangga, 2016)
Business Competition encourages entrepreneurs to have competence in managing the business. Start-up businesses will grow if it is able to manage the internal factors and external factors well. This study focuses on internal factors from the perspective of companies consisting of four components, namely marketing, human resources, finance, and operations. The second focus of this study is the external factor of a business seen from the approach five forces Porter lists five essential components of the external factors, namely: barriers to entry in the industry, threat from substitute products, threat from suppliers bargaining power, threat from buyers bargaining power, Among existing industry and rival firms. The object of this study is a start-up business in the city of Surabaya. This study used descriptive qualitative method with the aim of optimizing the management view of internal and external factors in the success of a start-up business seen from the perspective of the company. Validation of the results using triangulation techniques using: parisipatif observation, interview, and documentation (photos and interviews) to the informant (object) research. The results showed the management of internal factors (marketing, human resources, finance, and operational) and external (barriers to entry in the industry, threat from substitute products, threat from suppliers bargaining power, threat from buyers bargaining power, and rival Among existing industry firms ) is an important component that must be optimized in order to support the success of start-up businesses.